Does learning style influence academic performance in different forms of assessment?. Issue 3 (31st October 2013) - Wilkinson, Tracey; Boohan, Mairead; Stevenson, Michael
Abstract Educational research on learning styles has been conducted for some time, initially within the field of psychology. Recent research has widened to include more diverse disciplines, with greater emphasis on application. Although there are numerous instruments available to measure several different dimensions of learning style, it is generally accepted that styles differ, although the qualities of more than one style may be inherent in any one learner. But do these learning styles have a direct effect on student performance in examinations, specifically in different forms of assessment? For this study, hypotheses were formulated suggesting that academic performance is influenced by learning style. Using the Honey and Mumford Learning Style Questionnaire, learning styles of a cohort of first year medical and dental students at Queen's University Belfast were assessed. Pearson correlation was performed between the score for each of the four learning styles and the student examination results in a variety of subject areas (including anatomy) and in different types of assessments – single best answer, short answer questions and Objective Structured Clinical Examinations. In most of the analyses, there was no correlation between learning style and result and in the few cases where the correlations were statistically significant, they generally appeared to be weak. It seems therefore from this study that although the learning styles of students vary, they have little effect on academic performance, including in specific forms of assessment.